Tanzania Economic Update, December 2019 : Realizing the Potential of Agriculture for Inclusive Growth and Poverty Reduction - World Bank (Washington, DC: World Bank, 2022)
Tanzania was again one of the top growth performers in the region. Official GDP figures show that growth remained steady in the first half of the year, driven by higher public investment and by a recovery in exports. Inflation has been low and stable, and the balance of payments is quite sound despite a widening current account deficit. Exports are recovering from last year’s contraction. The Government's Tanzania Development Vision 2025 and the Five-Year Development Plan (FYDP II) set out ambitious goals for reducing poverty and sustainably industrializing so that the country can achieve middle-income status by 2025. The government recognizes agriculture as central to realizing its objectives of socioeconomic development, which are well-articulated in the Second Agriculture Sector Development Program (ASDP II). Among the goals of ASDP II are to transform agriculture by promoting commercialization, prioritizing high-potential commodity value chains, and mobilizing capital by giving the formal private sector a growing role in agriculture. Because agriculture and related value chains drive two-thirds of all jobs—three-quarters for the poor— the sector is central to creating more and better jobs at scale and significantly reducing poverty.